2022
DOI: 10.3389/fcell.2022.913110
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Small Extracellular Vesicles in Multiple Diseases: Biogenesis, Function, and Therapeutic Applications

Abstract: Macrophages (Mφs), as immune cells, play a pivotal role against pathogens and many diseases, such as cancer, inflammation, cardiovascular diseases, orthopedic diseases, and metabolic disorders. In recent years, an increasing number of studies have shown that small extracellular vesicles (sEVs) derived from Mφs (M-sEVs) play important roles in these diseases, suggesting that Mφs carry out their physiological functions through sEVs. This paper reviews the mechanisms underlying M-sEVs production via different for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 161 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…In addition, M1 is inflammatory, usually induced by IFN-γ, TNF-α or LPS and expresses specific markers, such as iNOS, CD86, CD16/32, TNF-α, IL-6 and so on. [43] iNOS is not only a key enzyme to induce NO secretion, but also an important downstream factor of NF-kB signaling pathway, which can respond to inflammatory stimulation. [44] TNF-α plays an indispensable role in regulating immune cells and inflammatory responses, and TNF-α dysregulation can cause inflammatory responses such as fever, edema and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, M1 is inflammatory, usually induced by IFN-γ, TNF-α or LPS and expresses specific markers, such as iNOS, CD86, CD16/32, TNF-α, IL-6 and so on. [43] iNOS is not only a key enzyme to induce NO secretion, but also an important downstream factor of NF-kB signaling pathway, which can respond to inflammatory stimulation. [44] TNF-α plays an indispensable role in regulating immune cells and inflammatory responses, and TNF-α dysregulation can cause inflammatory responses such as fever, edema and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Phalloidin staining showed that dendrocandin U could significantly improve the inflammatory morphological changes of macrophages (Figure 4), which was related to the inhibition of their transformation to M1 phenotype. In addition, M1 is inflammatory, usually induced by IFN‐γ, TNF‐α or LPS and expresses specific markers, such as iNOS, CD86, CD16/32, TNF‐α, IL‐6 and so on [43] . iNOS is not only a key enzyme to induce NO secretion, but also an important downstream factor of NF‐κB signaling pathway, which can respond to inflammatory stimulation [44] .…”
Section: Discussionmentioning
confidence: 99%
“…8 sEVs, with a diameter of 30-200 nm, are released by different cells, originate from the endocytic pathway 7 and widely distributed in a variety of body fluids. 9,10 All cells can release sEVs regardless of whether they are in a state of normal or pathological conditions. Due to their different sizes, levels, contents and origins, sEVs have great heterogeneity and target specific organs or cells, leading to different biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…EVs are produced by various immune cells, including B and T cells, macrophages, dendritic cells (DC), natural killer (NK) cells, mast cells, and thymocytes [ 164 , 214 , 215 , 216 , 217 , 218 ] and are rich in proteins with immune functions, such as antigen-presenting molecules (major histocompatibility complex (MHC) class I, MHC class II, CD1), adhesion molecules (CD11b, intercellular adhesion molecule 1 (ICAM-1)), and co-stimulatory proteins (CD86) [ 219 , 220 , 221 , 222 ]. Additionally, exosomes are involved in releasing intracellular components to the outside of cells as waste products, and through their loaded immune-related molecules, they have various immune functions, such as antigen presentation, including the priming of early T cells, differentiation of mature T cells, development of effector functions, and regulation of immune-related cells [ 223 , 224 , 225 , 226 , 227 ].…”
Section: Introductionmentioning
confidence: 99%